Large and temperature-stable anomalous Nernst effect under a favorable out-of-plane thermal gradient in the epitaxial Heusler spin gapless-like CoFeMnSi thin film. (18th October 2019) - Fu, Huarui; You, Caiyin; Ma, Li; Tian, Na
Abstract: Waste heat accounts for the large amount of energy consumption among the world development. The thermoelectric power techniques, such as Seebeck effect or anomalous Nernst effect (ANE)-based technologies, are highly accepted to be promising to harvest the waste heat. However, the thermally generated voltage from the single pair unit of the above devices is usually very small, which requires potential materials with high thermoelectric effect and facile device configuration for designing the thermopile module. In this work, we demonstrated that the spin gapless-like Heusler CoFeMnSi epitaxial film exhibits a large ANE under an out-of-plane thermal gradient, which is highly favorable for designing the thermopile module to realize a large electric voltage. Considering the less saturated magnetization of CoFeMnSi (∼530 emu/cc), a much larger value of ANE coefficient of the current CoFeMnSi film can be expected in comparison to the normal ferromagnetic metals, such as Co, Fe or their alloys. Moreover, we found that the ANE is dependent of the structural ordering; the ANE exhibits a relatively large value within a wide temperature range rather than the dramatic weakness at low temperature for the reported materials; the temperature-dependent ANE is closely related to the anomalous Hall effect of CoFeMnSi film.